Rational Design of Prevascularized Large 3D Tissue Constructs Using Computational Simulations and Biofabrication of Geometrically Controlled Microvessels. Issue 13 (18th May 2016) - Arrigoni, Chiara; Bongio, Matilde; Talò, Giuseppe; Bersini, Simone; Enomoto, Junko; Fukuda, Junji; Moretti, Matteo
Abstract : A major challenge in the development of clinically relevant 3D tissue constructs is the formation of vascular networks for oxygenation, nutrient supply, and waste removal. To this end, this study implements a multimodal approach for the promotion of vessel‐like structures formation in stiff fibrin hydrogels. Computational simulations have been performed to identify the easiest microchanneled configuration assuring normoxic conditions throughout thick cylindrical hydrogels (8 mm height, 6 mm ∅), showing that in our configuration a minimum of three microchannels (600 μm ∅), placed in a non‐planar disposition, is required. Using small hydrogel bricks with oxygen distribution equal to the microchanneled configuration, this study demonstrates that among different culture conditions, co‐culture of mesenchymal and endothelial cells supplemented with ANG‐1 and VEGF leads to the most developed vascular network. Microchanneled hydrogels have been then cultured in the same conditions both statically and in a bioreactor for 7 d. Unexpectedly, the combination between shear forces and normoxic conditions is unable to promote microvascular networks formation in three‐channeled hydrogels. Differently, application of either shear forces or normoxic conditions alone results in microvessels outgrowth. These results suggest that to induce angiogenesis in engineered constructs, complex interactions between several biochemical and biophysical parameters have to be modulated. Abstract : Vascularization of thick 3D constructs is a key challenge in tissue engineering . This paper presents a multimodal approach for the generation of prevascularized fibrin hydrogels based on computational simulations of oxygen distribution, biofabrication, and dynamic co‐culture systems, highlighting different effects on microvessel outgrowth depending on the combination of shear stress and oxygen concentration.